ASSOCIATION OF LIPID PROFILE WITH BODY FAT PERCENTAGE AND BMI IN SECOND TRIMESTER OF PREGNANCY - Syed Tousif Ahmed; Hira Attique; Moazam Shahid; Leena Hani; Rehana Rahman; Shahina Ishtiaque (ziauddin University, 2024)
ABSTRACT   Background: Variations in lipid profile are associated with body fat and BMI. In pregnancy, there is an increased demand of nutrients, especially for fats, for fetal development and its growth, which may disturb lipid metabolism. The objective of this study was to find out the associations between maternal body fat percentage (fat%) and BMI with lipid profile during second trimester of pregnancy.   Methods: A cross sectional study was designed on pregnant women of second trimester. These patients were recruited from gynae OPD during their antenatal checkup. After an informed consent Fasting blood samples were taken, BMI and body fat was calculated using Omron 308C body fat analyzer. Serum was extracted and lipid profile was analyzed on automated spectrophotometer analyzer at 546nm wavelength.   Results: A total of 84 patients were selected. Cholesterol was highest in younger age (<20). TGs were generally high in all age groups. Patients with low BMI (less than 18), had normal lipid profile, whereas, normal and high BMI patients had high cholesterol, TGs, LDL, HDL and VLDL. Obese had higher values for TGs, HDL, and VLDL with cholesterol on the upper limit. Cholesterol, in obese patients with very high body fat percentage, was not found elevated, but the results were not statistically significant. However, patients with body fat values as low, normal and high, all had high levels of cholesterol TGs, HDL and VLDL, statistically showing no difference.   Conclusion: Lipid profile and BMI were found independent variables having no association with body fat percentage during second trimester of pregnancy.